Pendidikan Islam dan Teknologi Digital dalam Mendukung Teory Taxonomy Bloom - Ridwan, Ridwan (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2018)
Digital technology plays an important role for the 21st century in helping human activities with the type and kinds of works. In Islamic terminology, the technological advancement as a platform for everyone to pay "shadaqoh" and getting information and knowledge as well as need. The world has always been inverted with the internet , covering a wide range of applications needed by humans. Applications is like google, facebook, yahoo, e-mail, whatsaap, Instagram, twiter, blogs and others are very easily accessible in various places without insulation. Implementing of Taxonomy Bloom through digital technology is a necessity. The domains of cognitive and psychomotor learning can be linked to the internet application of the constrained hierarchy of the taxonomy. Examples of Word, Excell, Power Point, Chrome, Mozilla Firefox, Internet Explorer, Facebook, Twitter, Instagram, Goolgle, Yahoo, MSN can be applied to the realm of cognitive learning by remembering, understanding, analyze (analyze), evaluate (evaluate) and create (creat) as a form of the realization of learning outcomes based on digital technology. Applications that can be applied include to distribute the material, reroute, submit opinions on some articles online by using the application in accordance with the facilities or softwere relevant to produce products such as making bullet, pointing, create a social networking group or provide a brief comment on the article in webs available. The purpose of this paper is to analyze the development of world technology. Communicate the progress of digital technology in the world of Islamic education and how to apply and utilization to support the application of Taxonomy Bloom's theory.